2000
DOI: 10.1017/s0033291799001403
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenics know more than they can tell: probabilistic classification learning in schizophrenia

Abstract: Patients with schizophrenia were able to establish representations of complex categories, but these remained unconscious. This is consistent with earlier reports, suggesting damaged explicit and spared implicit memory in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
49
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 35 publications
(52 reference statements)
9
49
1
Order By: Relevance
“…This result is consistent with the finding of several studies (Keri et al 2000;Weickert et al 2002;Beninger et al 2003;Keri et al 2005) indicating that the gradual acquisition of probabilistic contingencies in schizophrenia patients may be relatively intact, as well as the idea that different neural systems may support rapid and gradual feedback integration. The gradual integration of probabilistic feedback over many trials seems to rely more on the basal ganglia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the finding of several studies (Keri et al 2000;Weickert et al 2002;Beninger et al 2003;Keri et al 2005) indicating that the gradual acquisition of probabilistic contingencies in schizophrenia patients may be relatively intact, as well as the idea that different neural systems may support rapid and gradual feedback integration. The gradual integration of probabilistic feedback over many trials seems to rely more on the basal ganglia.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, there is evidence that the gradual acquisition of probabilistic contingencies depends more heavily on subcortical structures in the basal ganglia, and less on cortical structures (Knowlton et al 1996;Seger and Cincotta 2005). The results of multiple studies (Keri et al 2000;Weickert et al 2002;Beninger et al 2003;Keri et al 2005) suggest that the acquisition of probabilistic contingencies in schizophrenia patients may be relatively unimpaired, perhaps indicative of a relatively intact basal ganglia function in schizophrenia. Thus, patients with SZ could show intact initial discrimination learning, but impaired reversal learning.…”
mentioning
confidence: 99%
“…Priming has also been obtained in schizophrenia with a variety of other procedural tests, such as serial reaction time, where the subjects press one of four keys corresponding to stimuli that appears in one (of four) positions on a screen (Green, Kern, & Williams, 1997); or on a probabilistic classification task, in which subjects decide whether a set of four geometrical shapes are predictive of hypothetical weather conditions of rain or sunshine (Keri et al, 2000). All these studies found a dissociation effect.…”
Section: Palabras Clave: Facilitación Memoria Implícita Esquizofrenmentioning
confidence: 99%
“…These results have been inter-preted as supporting the claim that there are separate memory systems for declarative memory (in the medial temporal lobes) and nondeclarative learning (in the basal ganglia). Other studies of the weather prediction task have demonstrated severe impairments in patients with schizophrenia (Keri et al 2000; T. Weickert, T. Goldberg, A. Terrazas, L. Bigelow, J. Malley, M. Egan, and D. Weinberger, in prep.). Functional brain imaging by Poldrack and colleagues has shown that the medial temporal lobes become active early during learning of the weather-prediction task, and gradually become deactivated as the task is learned; conversely, the basal ganglia are inactive early in learning, but gradually become active (Poldrack et al 1999(Poldrack et al , 2001).…”
mentioning
confidence: 96%